Modeling planar pantographic sheets using a nonlinear Euler–Bernoulli beam element based on B‐spline functions. Issue 1 (17th December 2018) - Capobianco, Giuseppe; Eugster, Simon R.; Winandy, Tom
Abstract: An undeformed pantographic sheet consists of two orthogonal arrays of straight fibers interconnected by internal pins. In this paper, we model the fibers of this lattice‐like sheet as nonlinear Euler–Bernoulli beams and use B‐spline functions for their finite element discretization. Using the concept of one‐dimensional generalized force laws, we show how different models for the pins can be introduced in the model. Finally, the simulation of a tensile test is presented.